Factor adjustments after deregulation: panel evidence from Colombian plants - Marcela Eslava; John Haltiwanger; Adriana D. Kugler; Maurice Kugler (Institute for the Study of Labor (IZA), 2005)
In this paper, we analyze employment and capital adjustments using a panel of plants from Colombia. We allow for nonlinear adjustment of employment to reflect not only adjustment costs of labor but also adjustment costs of capital, and vice-versa. Using data from the Annual Manufacturing Survey, which include plant-level prices, we generate measures of plant-level productivity, demand shocks, and cost shocks, and use them to measure desired factor levels. We then estimate adjustment functions for capital and labor as a function of the gap between desired and actual factor levels. As in other countries, we find non-linear adjustments in employment and capital in response to market fundamentals. In addition, we find that employment and capital adjustments reinforce each other, in that capital shortages reduce hiring and labor shortages reduce investment. Moreover, we find that the market oriented reforms introduced in Colombia after 1990 increased employment adjustments, especially on the job destruction margin, while reducing capital adjustments. Finally, we find that while completely eliminating frictions from factor adjustments would yield a dramatic increase in aggregate productivity through improved allocative efficiency, the reforms introduced in Colombia generated only modest improvements.
Keywords: E22; E24; O11; C14; J63; 330; joint factor adjustment; irreversibilities; adjustment costs; input reallocation; deregulation; Deregulierung; Schock; Beschäftigungseffekt; Industrielle Beschäftigung; Kolumbien; Indien